Dukungan Perpustakaan dalam Proses Pembelajaran Online di Universitas Islam Negeri Sunan Kalijaga pada Masa Pandemic Covid-19 - Kusuma, Arja (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
During the COVID-19 pandemic, teaching and learning activities at UIN Sunan Kalijaga took place with an online learning system. This has received mixed responses from the public, there are pros and cons. The response is inseparable from the readiness of supporting facilities, one of which is the readiness of the library, the library in teaching and learning activities has an important role, especially in terms of meeting the information needs of students. Therefore, library support in the online learning process at UIN Sunan Kalijaga during the COVID-19 pandemic is needed. The purpose of this research is to find out how they support of Sunan Kalijaga UIN Library in the online learning process at UIN Sunan Kalijaga during the COVID-19 pandemic. This research uses descriptive qualitative method, the instrument in this study is the researcher himself, data collection techniques with interviews and documentation, the informant in this study is the head of the library of UIN Sunan Kalijaga. The results of this study are library support in the online learning process at UIN Sunan Kalijaga during the COVID-19 pandemic determined in a policy based on university policy. The contents of the policy that are directly related to library support in the online learning process at UIN Sunan Kalijaga are (1) the library encourages users to maximize the use of e-resources in the Sunan Kalijaga UIN Library, (2) Libraries open online services via whatsApp and media social is related to information needs that might not be found in e-resource services. Furthermore, the library provides support in the form of socialization related to the policy, on social media Instagram, Facebook, and YouTube.Keywords: library support, online Learning, COVID-19 Selama masa pandemic COVID-19, kegiatan belajar mengajar di UIN Sunan Kalijaga berlangsung dengan sistem pembelajaran online. Hal tersebut mendapat tanggapan yang beragam dari masayarakat ada yang pro dan kontra. Tanggapan tersebut tidak terlepas dari kesiapan failitas pendukung, salah satunya adalah kesiapan perpustakaan, perpustakaan dalam kegiatan belajar mengajar memiliki peran penting, terutama dalam hal pemenuhan kebutuhan informasi bagi mahasiswa. Oleh karena itu, dukungan perpustakaan dalam proses pembeljaran online di UIN Sunan Kalijaga pada masa pandemic COVID-19 sangat dibutuhkan. Tujuan dari penelitian ini, untuk mengetahui bagaimana dukungan yang dilakukan Perpustakaan UIN Sunan Kalijaga dalam proses pembelajaran online di UIN Sunan Kalijaga pada masa pandemic COVID-19. Penelitian ini menggunakan metode kualitatif deskriptif, instrument dalam penelitian ini adalah peneliti sendiri, teknik pengumpulan data dengan wawancara dan dokumentasi, informan dalam penelitian ini adalah kepala perpustakaan UIN Sunan Kalijaga. Hasil dari penelitian ini adalah dukungan perpustakaan dalam proses pembelajaran online di UIN Sunan Kalijaga pada masa pandemic COVID-19 ditetapkan dalam sebuah kebijakan yang berdasarkan pada kebijakan universitas. Adapun isi dari kebijakan yang berkaitan langsung dengan dukungan perpustakaan dalam proses pembeljaran online di UIN Sunan Kalijaga adalah (1) perpustakaan mendorong pemustaka untuk memaksimalkan penggunaan e-resource yang ada di Perpustakaan UIN Sunan Kalijaga, (2) Perpustakaan membuka layanan online via whastapp dan media sosial terkait dengan kebutuhan infromasi yang mungkin tidak ditemukan pada layanan e-resource. Selanjutnya perpustakaan melakukan dukungan dalam bentuk sosialisasi terkait kebijakan tersebut, di media sosial Instagram, facebook dan youtube. Kata Kunci: dukungan Perpustakaan, pembelajaran online, COVID-19